Acute Febrile Illness Surveillance and Dengue–Chikungunya Seroprevalence in Selected Community Clusters of Visakhapatnam: A Prospective Cohort Study - PJ, Srinivas; KK, Lakshmi Prasad; B, Aruna; A, Krishna Veni; P, Radha Kumari; S, Chandrika (Archives of Clinical and Biomedical Research, 2025)
Introduction: Vector-borne Acute febrile illness (AFI) is common in India. Dengue and Chikungunya are endemic in certain regions. The present study was planned to describe the sero-epidemiology of dengue and chikungunya in selected community clusters near Visakhapatnam, Andhra Pradesh. Subjects and Methods: Community-based AFI episodes of dengue and chikungunya were studied using a cohort design across five endemic clusters in Visakhapatnam. House surveys were undertaken to identify AFI cases with follow-up for 1 year. All febrile episodes were investigated using rapid diagnostic tests and laboratory-based assays. At baseline and at 12 months, a serosurvey was undertaken to estimate levels of IgG, IgM, and neutralizing antibodies associated with infections. Socio-economic status data were also collected in this survey. Results: A total of 766 participants from the five community clusters were enrolled, of which 262 reported fevers during the one-year surveillance. 52 (19.8%) episodes of AFI were identified among 262 fever reports. Five cases each (1.9% of AFI episodes) were laboratory-confirmed as dengue and chikungunya. At baseline, 91% and 60% subjects were Dengue and Chikungunya IgG-positive, respectively. At 12 months, 92% of subjects were Dengue IgG-positive and 58% were Chikungunya IgG-positive. Conclusion: Although the number of active cases for both Dengue and Chikungunya was very small, high seroprevalence suggests long-standing endemic transmission and substantial background immunity in the study clusters.